Emerging Strategies and Therapeutic Advances in Influenza Treatment: A Comprehensive Review - Alrizg, Saeed Ali SAEED; Ali Alsalem , Abdullah Saad; Alyami , Hussain Ali; al Shaybah, Mohammed Hussain Saleh; Alyami , Amal Saeed; Al Hammam, Mohammed Ali; Almeel , Zahra Hani Jarallah; Alslom, Mahdi Mohammed Ali A; Al yami, Ghazi Hadi Mohammed; Alhassan, Abdullah Saleh Omar (Journal of Ecohumanism, 2024)
Influenza remains a significant global health challenge, causing annual epidemics and occasional pandemics that impact millions worldwide. While current antiviral drugs and seasonal vaccines offer some protection, their limitations—such as drug resistance, variable efficacy, and evolving viral strains—highlight the urgent need for new therapeutic approaches. This review explores recent advancements in influenza treatment, including novel antiviral drugs, combination therapies, host-targeted treatments, monoclonal antibodies, and innovative delivery methods using nanotechnology. Emerging experimental therapies, such as RNA-based treatments and universal vaccines, offer promising avenues for enhanced, broad-spectrum protection. Additionally, the review discusses mechanisms of viral resistance to current treatments and potential solutions to overcome these barriers. These advancements could significantly improve clinical outcomes and inform future strategies for managing influenza. By addressing gaps in current treatments and advancing the development of innovative approaches, this review emphasizes the importance of a multifaceted approach to influenza management.